(untitled) (Journal of Information Technologies in Education (ITE), 2020)
The article explores the prospects of the introduction of cloud technologies in higher education, reveals the advantages and disadvantages of using cloud technologies in higher education. Itis determined that therelevance of the use of cloud technologiesin education is that they not only perform the functions of tools, but also provide qualitatively new learning opportunities, the formation of skills of independent learning activities, contribute to the creationof new forms of learning and education. Itis proved that competently built educational process allows to solve the main goal set by the higher school: qualitative preparation in the chosen direction of study for becoming and development of a competitive specialist. The basic direction of introduction of cloud technologies in the educational process of high school is defined qualitative preparation in the chosen direction of study for the formation and development of a competitive specialist in the professional ISSN1998-6939. Information Technologies in Education. 2020. No 1(42)31field. The most common ways of working with cloud technologies in educational institutions are identified, such as distance learning, student collaboration on projects and documents. The virtual space of the university, which aims at supporting the distance learning, management and optimization of business processes of higher education, is outlined. The cloud model, which promotes accessibility, is characterized by five basic elements, such as self-service, compatible resource, network access, separatelocation, flexibility, measured services.It is determined that the use of cloud technologies in the educational process of higher education is an important step, especially in the conditions of limited resources and the constant need for updating both software and technical component of computing laboratories, which provides the possibility of using cloud technologies and will allow to support the computer equipment of higher education facilities at a high modern level with minimalcost. It is emphasizedthat the only vulnerability of innovation is the complexity of regularly installing broadband Internet access.